Sequence and phylogenetic analysis of the mitochondrial genome of giant clam, Tridacna crocea (Tridacninae: Tridacna) - Shanya Cai; Wendan Mu; Hui Wang; Jiawei Chen; Haibin Zhang (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we first determined and described the mitochondrial genome of Tridacna crocea, a member of the subfamily Tridacninae. The existing mitogenome of T. crocea is 19,157 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 24 tRNA genes, and 1 non-coding control region. Phylogenetic analysis revealed that T. crocea was closely related to T. squamosa.